The impact of fire drills on firefighters’ performance - Matome R. Ramohale; Botshelo B. Mokaleng; Nthai Monnye (Jàmbá)
Firefighting is one of the most physically demanding, dangerous, and stressful jobs, constituting several physical activities, which include moving equipment up the stairs in tall buildings and deploying charged hoses. In fire management, structured training exercises are fire drills used to prepare staff for successful responses to fires situations. Firefighters, emergency responders, and other pertinent people can practice responding to a real fire by simulating real-life fire events. However, South African fire departments and stations, particularly in Mpumalanga, Nkangala district, are failing to comply with the regulations because they are not conducting these fire drills once a month. This failure to conduct fire drills has resulted in the loss of skills and knowledge. Poor service delivery has become the norm and prevalent. This study aimed to investigate if fire drills can improve the operational efficacy and psychological state of firefighters. The study adopted a quantitative research approach and collected data from randomly sampled participants who work at fire stations located in Nkangala district in Mpumalanga province in South Africa. The Wilcoxon signed-rank statistical test revealed that fire drills do improve operational efficacy and the psychological state of firefighters, demonstrating that fire drills are a key component of fire department’s performance. This study recommends that fire drills must be mandatory for fire departments in South Africa.